Volume 5B: Heat Transfer 2016
DOI: 10.1115/gt2016-57296
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in Flow Parameter Resulting From Volcanic Ash Deposition in Engine Representative Cooling Passages

Abstract: Internal cooling passages of turbine blades have long been at risk to blockage through the deposition of sand and dust during fleet service life. The ingestion of high volumes of volcanic ash therefore poses a real risk to engine operability. An additional difficulty is that the cooling system is frequently impossible to inspect in order to assess the level of deposition. This paper reports results from experiments carried out at typical HP turbine blade metal temperatures (1163K to 1293K) and coolant inlet te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Working up to 1350 C as a temperature inlet, the authors show different deposition patterns on the turbine nozzle. Wylie et al [240] reported the results of particle deposition in the internal cooling passage of a high-pressure turbine. The authors perform particle deposition using actual volcanic ash.…”
Section: Perspectivesmentioning
confidence: 99%
“…Working up to 1350 C as a temperature inlet, the authors show different deposition patterns on the turbine nozzle. Wylie et al [240] reported the results of particle deposition in the internal cooling passage of a high-pressure turbine. The authors perform particle deposition using actual volcanic ash.…”
Section: Perspectivesmentioning
confidence: 99%